Hybrid intelligent systems for information retrieval - Thakare, Anuradha, 1978-; Laddha, Shilpa; Pawar, Ambika (Boca Raton : Chapman & Hall/CRC Press, 2023)
"With the digitization of the entire world, the data gets generated at a fast pace. Extracting and retrieving useful information and patterns becomes challenging as information is not always in structured form. Therefore, there is a need for the design and development of Hybrid Intelligent Information Retrieval System. Broadly four approaches are covered in this book for design and development of Intelligent Information Retrieval: 1. Evolutionary approach for optimal Information Retrieval, 2. Novel Matching functions for Information Retrieval, 3. Natural Language Processing for Modern Information Retrieval 4. Development of Semantically enhanced Web Information Retrieval"--
OCLC-licensed vendor bibliographic record.
Keywords: Information storage and retrieval systems; Hybrid computers; Soft computing; COMPUTERS / Database Management / Data Mining; COMPUTERS / Information Technology